The Rohingya Crisis and the Practices of Erasure. Issue 1 (2nd January 2019) - MacLean, Ken
ABSTRACT: The essay utilized two concepts, lawfare and spacio-cide, to place different facets of "belonging" into conversation with one another. The concepts highlight how the progressive erasure of citizenship shapes the progressive erasure of home and vice-versa, with the result being the largest cross-border humanitarian crisis in Asia today. The first section of the essay situates the Rohingya crisis within the broader politico-military context. It illustrates the ways in which the patterns of violence are and are not consistent with the practices the state's armed forces have used against different ethnic populations in other parts of the country. The second section traces how successive laws and policies transformed the Rohingya into the largest stateless population in the world. The final section summarizes the tactics used to segregate, dispossess, and, ultimately, drive Rohingya from the countryside. The practices of erasure, the essay concludes, are the most recent iteration of an ongoing cycle of persecution that began forty years ago and will likely continue in the future.